A tévedés jelentőségének egyes aspektusai az élet, testi épség elleni bűncselekmények körében - Mónusné Kiss, Katalin (Debreceni Jogi Műhely, 2007)
I examined one of the grounds for the preclusion of punishability and grounds for the termination of punishability, which is error. Grounds for the preclusion of punishability and grounds for the termination of punishability, mean that punishability shall be precluded. The error means- 27.§- the perpetrator shall not be punishable for a fact, of which he was not aware on perpetration. The person, who commits an act in the erroneous hypothesis that it is not dangerous for society and who has reasonable ground for this hypothesis, shall not be punishable. Error shall not exclude punishability, if it is caused by negligence, and the law also punishes perpetration deriving from negligence. I examined how often the judge accept an error, if the person believe that he’s in the right, because he was attecked, or direct emergency menace. Or maybe he believes, that he is in danger of his life. Is it exceptional or not? What examine judge? It isn’t only hypothetical question, because very complicated task for the judge.